DIVERSITY, ECOLOGY AND CONSERVATION STATUS OF NEPENTHES IN WEST SUMATRA PROVINCE, INDONESIA - Mansur, Muhammad; Salamah, Andi; Mirmanto, Edi; Brearley, Francis Q (SEAMEO BIOTROP, 2023)
Nepenthes is the largest carnivorous plant genus present in Indonesia. There are 39 species of Nepenthes pitcher plants recorded in Sumatra from lowland to montane forests, and 34 of them are endemic; this represents the greatest species diversity of Nepenthes after Borneo. Field studies were conducted in 2021 and 2022 to increase our knowledge of the diversity, habitats and distributions of Nepenthes in West Sumatra province. Twenty-three species of Nepenthes were recorded from the province, consisting of 15 highland species, 4 mid-elevation species and 4 lowland species. Ecophysiological studies conducted at Bukit Malalak showed clumped distributions of N. bongso, N. dubia, N. eustachya and N. rhombicaulis. Foliar and pitcher fluid nutrient concentrations were found to be similar to those cited in other recent studies although growth rates were slightly more rapid than at Gunung Talang. Bukit Malalak is a new locality for two threatened species, namely N. dubia (CR) and N. rhombicaulis (VU), enlarging their extents of occurrence. In total, nine species from West Sumatra are threatened and conservation actions are urgently needed for these and other Nepenthes species remaining on the island.